2018
DOI: 10.1016/j.pec.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Findings from a feasibility study to improve GP elicitation of patient concerns in UK general practice consultations

Abstract: GPs can solicit early for additional concerns and GPs can establish patients' additional concerns in the opening of the consultation, which can help to plan and prioritise patients multiple concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The current results concur with past research, which found that when patients are free to express themselves, they are likely to initiate between 2–3 concerns [ 26 , 27 ]. This is consistent with the current study where non-PCI patients raised on average 2.9 concerns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current results concur with past research, which found that when patients are free to express themselves, they are likely to initiate between 2–3 concerns [ 26 , 27 ]. This is consistent with the current study where non-PCI patients raised on average 2.9 concerns.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was not in the expected direction, where it was predicted that consultants in the PCI group would refer to the concerns highlighted by the patient (raised when completing the PCI) and initiate the first concern accordingly. However, literature suggests that consultants will begin with an open question such as “How can I help you today?” [ 27 ], where patients will reply with the initiation of the first concern [ 32 ]. Our results show this to be consistent regardless of the PCI being used to highlight concerns pre-consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Additional concerns are medical problems (Byrne and Long, 1976) that are prima facie unrelated to the main reason for the visit. Consequently, interventions have been developed to help physicians better solicit additional concerns from patients (Heritage and Robinson, 2011;Robinson et al, 2016;Leydon et al, 2018;Stuart et al, 2018). What has not yet been studied is when and how physicians initiate additional concerns and what functions they serve.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that missed diagnoses10 11 are often related to inadequate symptom elicitation12 and doctors’ elicitation and interpretation of the presenting problem is critical for subsequent referral decisions 13 14. However, elicitation can often be incomplete,15 16 and if doctors do not ask for information, patients often do not provide it 17 18. Despite a vast existing body of research exploring the conversation between patients and doctors,19 which is embedded within doctor communication training (eg, the Calgary-Cambridge model),20 there is a lack of in-depth research on doctor-patient interactions to elucidate the essential behavioural factors central to this diagnostic phase.…”
Section: Introductionmentioning
confidence: 99%